WHY FOREIGN LANGUAGE IS IMPORTANT FOR ENGINEERS? (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article is devoted to the discussion of promising areas of teaching English for students of technical specialties. It deals with the modern problem of university methodology. The main incentive for the development of language education can be considered the practical needs of business. The requirements for foreign language proficiency for university graduates are constantly increasing, but the study of foreign languages often remains at the same level. When developing programs in foreign languages, it is advisable to take into account the specifics of training in technical universities, the ratio of different models of language learning in them: for general purposes, academic and professional communication.